Comparison of Diatoms Which Were Obtained from The External Surface of The Body and Internal Organs in the Corpses Pulled Out of Water Using Colloidal Silica Gradient Centrifuge Method - Erkan, Çiler Fulya; Çetin, Gürsel (The Bulletin of Legal Medicine, 2019)
Objective: Diatom analysis is a valuable tool in forensic science and it is useful in diagnosis of drowning and determination of the drowning site. The basic principal of the “diatom test” in investigation of drowning is based on correlation between diatoms are present in the medium where the possible drowning took place and inhalation of water causes penetration of diatoms into the alveolar system and blood stream and consequently their deposition into brain, kidneys and other organs, like the bone marrow of large bones. There are various extraction methods that are used to isolate diatoms from water and tissues. Nitric acid digestion is a worlwide known method for the extraction of diatoms. In this study, instead of acid digestion method, colloidal silica gradient centrifuge method was used to extraction diatom and the advantages of this technique has been aimed to be discussed.Materials and Methods: Therefore, 30 visceral and body fluid samples that have been obtained from corpses which were removed from the water and brought to the Council of Forencic Medicine to perform autopsy, were examined and diatom were obtained from samples of 19 cases. Moreover, the diatoms that were obtained from the swab samples taken from the outer body surfaces and the diatoms obtained from the visceral organs were compared.Results:  When the diatoms which were obtained from internal organs tissues and body fluids were evaluated numerically, it was seen that the diatoms that were obtained lungs were in high numbers and it was followed by pleural liquid...
Keywords: Diatome; plankton; pericoll